Islamic Theology in the Turkish Republic (by Philip Dorroll) (American Journal of Islam and Society, 2022)
The book under review offers an analysis of Islamic theology delineated broadly under the auspices of the Ottomans and the nation-state of Turkey, in past and present. As outlined in its introduction, the book comprises five chapters: 1. Origins, 2. Nation, 3. God, 4. Humanity, 5. Futures.